Do patients want their families or their doctors to make treatment decisions in the event of incapacity, and why?. Issue 4 (1st October 2016) - Wendler, David; Wesley, Robert; Pavlick, Mark; Rid, Annette
ABSTRACT: Background : Current practice relies on patient-designated and next-of-kin surrogates, in consultation with clinicians, to make treatment decisions for patients who lose the ability to make their own decisions. Yet there is a paucity of data on whether this approach is consistent with patients' preferences regarding who they want to make treatment decisions for them in the event of decisional incapacity.Methods : Self-administered survey of patients at a tertiary care center.Results : Overall, 1169 respondents completed the survey (response rate = 59.8%). Of the 229 respondents who had previously designated a surrogate, 78.2% wanted their surrogate to make treatment decisions in the event of decisional incapacity, whereas 21.8% wanted their doctors to make treatment decisions. Of the 822 respondents who had not designated a surrogate, 66.1% wanted their family to make treatment decisions, whereas 33.9% wanted their doctors to make treatment decisions. The most common explanation provided for why respondents wanted their surrogate or family to make treatment decisions for them in the event of decisional incapacity was the belief that loved ones knew the patient's treatment preferences.Conclusions : Contrary to current practice, 33.9% of respondents who had not designated a surrogate and 21.8% of those who had designated a surrogate indicated that they wanted their doctors to make treatment decisions for them in the event of decisional incapacity. Moreover, many of those who wanted their surrogates or family members to make treatment decisions explained this preference by citing a belief that loved ones knew the patient's treatment preferences. This belief is undermined by prior research that suggests that surrogates and family members frequently are unable to predict which treatments their charges would want. Future research should assess these two concerns with current practice and, where necessary, identify approaches to address them.